PENGARUH INFLASI, PERTUMBUHAN EKONOMI, DAN TINGKAT PENDIDIKAN TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI SUMATERA UTARA - Aulia Anggi Lestari Saragih; Wijaya, Riko Setya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of inflation, economic growth, and education level on the open unemployment rate in North Sumatra Province. The open unemployment rate is an important indicator in assessing labor market conditions and the success of regional economic development. This study uses a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS) of North Sumatra Province during a specific research period and analyzed using the multiple linear regression method. Before the analysis was carried out, the data was tested through a classical assumption test to ensure the feasibility of the research model. The results of the study show that inflation, economic growth, and education level simultaneously have a significant effect on the open unemployment rate in North Sumatra Province. Partially, economic growth and education level have a significant influence on the open unemployment rate, while inflation has a relatively smaller influence. These findings show that sustainable economic growth and improvement in the quality of education can be an important strategy in reducing the open unemployment rate and improving people's welfare.